Gene-deficient mouse model established by CRISPR/Cas9 system reveals 15 reproductive organ-enriched genes dispensable for male fertility - Nguyen, Tuyen Thi Thanh; Tokuhiro, Keizo; Shimada, Keisuke; Wang, Haoting; Mashiko, Daisuke; Tonai, Shingo; Kiyozumi, Daiji; Ikawa, Masahito (Frontiers in Cell and Developmental Biology, 2024)
Since the advent of gene-targeting technology in embryonic stem cells, mice have become a primary model organism for investigating human gene function due to the striking genomic similarities between the two species. With the introduction of the CRISPR/Cas9 system for genome editing in mice, the pace of loss-of-function analysis has accelerated significantly. This has led to the identification of numerous genes that play crucial roles in male reproductive processes, including meiosis, chromatin condensation, flagellum formation in the testis, sperm maturation in the epididymis, and fertilization in the oviduct. Despite the advancements, the functions of many genes, particularly those enriched in male reproductive tissues, remain largely unknown. In our study, we focused on 15 genes and generated 13 gene-deficient mice [4933411K16Rik, Adam triple (Adam20, Adam25, and Adam39), BC048671, Cfap68, Gm4846, Gm4984, Gm13570, Nt5c1b, Ppp1r42, Saxo4, Sh3d21, Spz1, and Tektl1] to elucidate their roles in male fertility. Surprisingly, all 13 gene-deficient mice exhibited normal fertility in natural breeding experiments, indicating that these genes are not essential for male fertility. These findings have important implications as they may help prevent other research laboratories from duplicating efforts to generate knockout mice for genes that do not demonstrate an apparent phenotype related to male fertility. By shedding light on the dispensability of these genes, our study contributes to a more efficient allocation of research resources in the exploration of male reproductive biology.